Allah di Dunia Digital: Dampak Perubahan Pola Komunikasi terhadap Perspektif orang Kristen tentang Allah - Chandra, Robby Igusti; Dwiraharjo, Susanto (JURNAL TEOLOGI GRACIA DEO, 2022)
Past studies especially done by Walter Ong have shown that the changes in technology and culture could trigger the emergence of new patterns of communication and relationship that influence human self-understanding, the meaning of life, and the image of God that they believe. This article explores whether the rapid development of digital technology and culture in Indonesia can change the modern Christians’ image of God. By using literature research, it is found that the Indonesian Christians who are already immersed in the digital culture that emphasizes experiential reality, non-stop flexible relationships, and subjective nonphysical presence might prefer the Holy Spirit as God-image in their mind. They even wish for an experiential relationship with the Holy Spirit who relates to human beings in a nonphysical and flexible manner. This study gives hints for Indonesian churches to recognize some challenges in the theological and practical spheres that they have to face.  AbstrakStudi masa lalu misalnya dari Walter Ong telah menunjukkan bahwa, perubahan teknologi dan budaya memicu hadirnya pola komunikasi dan relasi yang berbeda sehingga mengubah pemahaman manusia mengenai dirinya, makna hidup, bahkan gambaran mereka mengenai Allah yang dipercayanya. Artikel ini meneliti apakah perubahan yang disebabkan oleh hadirnya teknologi dan budaya digital yang sangat cepat di Indonesia akan mengubah pandangan orang Kristen mengenai Allah. Dengan metode penelitian kepustakaan didapatkan temuan bahwa, orang-orang Kristen yang sudah terbiasa hidup dalam budaya digital yang menekankan realitas subjektif yang eksperinsial, relasi terus menerus, kehadiran non ragawi akan lebih mudah menghayati hubungan dengan Roh Kudus yang berelasi dengan manusia secara cair. Studi ini memberikan isyarat bagi gereja di Indonesia tenta tantangan-tantang yang perlu di jawab baik di ranah teologis maupun praktis.